Consumer Attitude towards High Protein Plant-Based Milk and an Evaluation of Its Shelf-life - Chaisuwan, Benchamat; Ploypetchara, Thongkorn; Budseekoad, Siriporn; Sorndech, Waraporn (Journal of Food Technology, Siam University, 2024)
The objective of this research was to develop a high-protein red bean milk product using concentrated red bean protein and a sterilization method. The ideas for the product development were taken from a study of consumer attitudes which used the laddering technique and the shelf-life of the product was also evaluated. The results of the study on the health and nutritional attitudes of 30 consumers found that consumers could be divided into 2 groups according to their health consciousness scores (Group 1 = 5.71 points and Group 2 = 3.63 points) and their interest in dairy products from plants (Group 1 = 5.86 points and Group 2 = 3.69 points). The attitudes of the Group 1 test-taker towards the red bean milk products were that it contained high protein, a delicious taste, was sweet without sugar, was not viscous, and had attractive packaging. The red bean milk formula was developed by adding 5.7 grams of concentrated red bean protein per 100 milliliters, so that it could claim to have a high protein content, according to the Ministry of Public Health Announcement (No. 445), 2023. The product shelf-life was studied under accelerated conditions at 35, and 45 degrees Celsius for 3 months. It was found that the products stored under these conditions at 35 and 45 degrees Celsius showed an increase in yellowness, while pH, total solid content, and consumer acceptance were significantly decreased. We assessed Q10 of the test by identifying a pH drop below 4.3 as an unacceptable criterion. It was found that the product has a shelf life of approximately 269.4 days at 25 degrees Celsius. Therefore, we can further utilize this research to develop plant-based milk products that align with consumer needs.